The necessity of ulnar osteotomy in children with missed Monteggia fractures - Zhang, Man; Zhou, Yu; Wang, Peikang; Zhang, Xinkai; Yao, Hailun; Li, Di; Liu, Xing (Frontiers in Pediatrics, 2025)
ObjectiveThe aims of this study were to review our cases of missed Monteggia fracture treated by open reduction of the radial head with or without ulnar osteotomy and to investigate the necessity of ulnar osteotomy in the surgical treatment of a missed Monteggia fracture.Materials and methodsThe children were divided into two groups according to the surgical method used. The patients in group A were treated with Kirschner wire or external fixation after ulnar osteotomy and Kirschner wire fixation after open reduction of the humeroradial joint. The patients in group B were treated with open reduction of the humeroradial joint and Kirschner wire fixation and ulnar osteotomy was not performed. The imaging results from the most recent postoperative follow-up were evaluated using the Nakamura grading criteria, and the patients’ elbow function was evaluated using the Mayo Elbow Performance Score (MEPS).ResultsThere were 53 patients in group A and 14 patients in group B. The mean age of the children in group A was older than that in group B and the time to diagnosis and treatment in group A was longer than that in group B. Regarding the Nakamura grading, there was no significant difference in the proportion of those that received an “excellent” postoperative score between group A and group B (p > 0.05). There was no significant difference in the MEPS post-operation between group A and group B (P > 0.05). In group A, the recorded complications included a postoperative dislocation of the humeroradial joint, a broken Kirschner wire in the humeroradial joint, occasional mild pain in the elbow joint, and Kirschner wire ends penetrating the patient’s subcutaneous tissue, all of which were treated through surgery. In group B, the recorded complications were a postoperative dislocation of the humeroradial joint, a broken Kirschner wire in the humeroradial joint, and myositis ossificans.ConclusionUlnar osteotomy is not necessary for all children with missed Monteggia fractures. Open reduction of the humeroradial joint followed by Kirschner wire fixation is a surgical option in younger patients with a short time to diagnosis and treatment .